(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Poultry farming is part of the productive chain of corn, soybeans and balanced, which is one of the most important within the Ecuadorian agricultural sector. Ecuadorian poultry farming has increased its production in recent years, unlike other types of meat production. The objective of the present investigation was to determine the effect of the addition of noni (Morinda citrofolia L.) foliage levels on the productive performance of Broiler chickens. The work was carried out in the "Cañales" Campus of the Mocache Canton, Los Ríos province. 160 Broiler Cobb 500 chickens were used, distributed in a completely randomized design with 4 treatments, 5 repetitions each, with 8 animals as the experimental unit. The evaluated treatments are T1 (Control; Commercial Balanced); T2, T3 and T4 (0.5, 1 and 1.5% respectively of Noni foliage flour). No statistical differences were found in relation to the productive parameters between the means of Tukey treatments (P≤0.05), however in the cost-benefit relation, 0.5% of Noni foliage presented the best value ( 1.27), which means that for every dollar invested, a profit of 0.27 cents was obtained, with a profitability of 27.49% and a mortality of 2.5%. While the control treatment obtained a value of 1.12; a profitability of 11.71% and a mortality of 5%.